Solving the Myxidium rhodei (Myxozoa) puzzle: insights into its phylogeny and host specificity in Cypriniformes - Baiko, Dariya; Lisnerová, Martina; Bartošová-Sojková, Pavla; Holzer, Astrid S; Blabolil, Petr; Schabuss, Michael; Fiala, Ivan (Parasite (Paris, France), 2024)
Myxidium rhodei Léger, 1905 (Cnidaria: Myxozoa) is a kidney-infecting myxosporean that was originally described from the European bitterling Rhodeus amarus. Subsequently, it has been documented based on spore morphology in more than 40 other cypriniform species, with the roach Rutilus rutilus being the most commonly reported host. This study introduces the first comprehensive data assessment of M. rhodei, conducted through morphological, ecological and molecular methods. The morphological and phylogenetic analyses of SSU rDNA sequences of Myxidium isolates obtained from European bitterling and roach did not support parasite conspecificity from these fish. In fact, the roach-infecting isolates represent three distinct parasite species. The first two, M. rutili n. sp. and M. rutilusi n. sp., are closely related cryptic species clustering with other myxosporeans in the freshwater urinary clade, sharing the same tissue tropism. The third one, M. batuevae n. sp., previously assigned to M. cf. rhodei, clustered in the hepatic biliary clade sister to bitterling-infecting M. rhodei. Our examination of diverse cypriniform fishes, coupled with molecular and morphological analyses, allowed us to untangle the cryptic species nature of M. rhodei and discover the existence of novel species. This underscores the largely undiscovered range of myxozoan diversity and highlights the need to incorporate sequence data in diagnosing novel species.
Keywords: Cypriniformes; parazitární nemoci u zvířat; DNA, Ribosomal; Myxozoa; Cyprinidae; Kidney-infecting Myxidium spp.; Host specificity; zvířata; Host Specificity; nemoci ryb; fylogeneze; ribozomální DNA; ledviny; Parasitic Diseases, Animal; Fish Diseases; Cryptic species; máloostní; Kidney; Phylogeny; PCR screening; hostitelská specificita; Animals